Implementasi Accurate Accounting Software dalam Meningkatkan Efisiensi Operasional pada Perusahaan Refraktori (Studi Kasus PT Menara Bukit Lubukkeli) - Ahmad Nurpuad; Safuan Safuan (Jurnal Pendidikan Indonesia, 2025)
In the face of globalization and rapid technological advancements, companies are under pressure to improve operational efficiency. This study examines the impact of implementing the Accurate management information system on operational efficiency at PT. Menara Bukit Lubukkeli. The research employs a descriptive qualitative methodology, analyzing data from literature reviews, case studies, and interviews. The findings demonstrate that the implementation of Accurate significantly enhances operational efficiency in several areas. First, the system reduces the time required to prepare financial statements, compile purchase and sales data, and manage inventory across warehouses and project sites. Second, it contributes to the reduction of operational costs, particularly by minimizing the need for external parties in preparing annual financial reports. Lastly, Accurate improves the accuracy of various reports, including financial statements, inventory, and project cash flow. The study concludes that Accurate has proven effective in enhancing both efficiency and accuracy in the company’s operational processes. These findings highlight the importance of adopting integrated management information systems to streamline business operations and improve overall performance.